2022
DOI: 10.21203/rs.3.rs-2251355/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary Supplementation of Chromium and Yeast in Deccani Sheep: Effect on Nutrient Digestibility, Nitrogen Balance and Plane of Nutrition

Abstract: The goal of the present study was to investigate the effect of dietary inclusion of chromium (Cr) and yeast individually and in-combination on nutrient digestibility, nitrogen balance and plane of nutrition in Deccani sheep. Thirty-six adult Deccani rams of 2-3 yrs of age with an average body weight of 27.68±1.08 kg were randomly divided into 6 groups consisting of 6 animals each in a completely randomized design. The experimental diets were as follows: 1. Control: Basal diet (BD) without any supplement, 2. 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested a potential correlation between the supplementation of Cr and improved immune competence and stress resistance (Vargas-Rodriguez et al, 2014;Leiva et al, 2015). combination of Cr and yeast significantly affected rumen fermentation pattern and in vitro nutrient degradability (Mohanty, 2022). Previous research has shown that providing chromium to goats increases nutritional consumption (Haldar et al, 2009;Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested a potential correlation between the supplementation of Cr and improved immune competence and stress resistance (Vargas-Rodriguez et al, 2014;Leiva et al, 2015). combination of Cr and yeast significantly affected rumen fermentation pattern and in vitro nutrient degradability (Mohanty, 2022). Previous research has shown that providing chromium to goats increases nutritional consumption (Haldar et al, 2009;Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%